The Problem of Junior High School Students in Learning Ratio of Two Variables and The Alternative Solving - Saryanto, Teguh (Journal of Mathematics and Mathematics Education, 2019)
Mastering of Competency in Explaining Ratio two variables and problem solving that is related to ratio two variables is very important. This competency is needed to understand Mathematics material/ subject for the next steps, and in real life, many problems that is related to ratio. The purpose of this research is to know the problems that are face by junior high school students in studying ratio in mathematics subject. This research methods uses qualitative case studying to know the student’s problem in ratio in this pandemic situation. There are 90 seventh students of junior high scholl 15 Surakarta as the subjects in this research. This instrument that is used in this research is mathematics test of ratio two variables. The test are developed from essay questions the analyze the students answer. The low capability in answering ratio two variables test is caused by the low of conceptual understanding, unaccuration in procedure and principle.